2022
DOI: 10.3390/ijms23126390
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Metabolome Analysis Provide New Insights into the Process of Tuberization of Sechium edule Roots

Abstract: Chayote (Sechium edule) produces edible tubers with high starch content after 1 year of growth but the mechanism of chayote tuberization remains unknown. ‘Tuershao’, a chayote cultivar lacking edible fruits but showing higher tuber yield than traditional chayote cultivars, was used to study tuber formation through integrative analysis of the metabolome and transcriptome profiles at three tuber-growth stages. Starch biosynthesis- and galactose metabolism-related genes and metabolites were significantly upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The expression data of ‘Tuershao’ root tubers of three different developmental stages (T1: early, T2: middle, and T3: mature stages) were obtained from our previous transcriptome data [ 22 ]. Briefly, the FPKM value of the MADS gene in transcriptome data was log2 standardized and displayed by heat map [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The expression data of ‘Tuershao’ root tubers of three different developmental stages (T1: early, T2: middle, and T3: mature stages) were obtained from our previous transcriptome data [ 22 ]. Briefly, the FPKM value of the MADS gene in transcriptome data was log2 standardized and displayed by heat map [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…The female flower of ‘Tuershao’ cannot expand into fruit normally, as with the chayote. The edible root tuber in the underground is its main product, and the root tuber yield is much higher than that of chayote [ 22 ]. For the tissue-specific expression analysis, we collected the roots, stems, leaves, tendrils, and open male and female flowers of ‘Tuershao’ and chayote; for floral organ development expression analysis, the male and female flower samples of ‘Tuershao’ and chayote with different diameters were collected and named S1 to S5, then immediately frozen in liquid nitrogen and stored at −80 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have suggested that the formation of root tuber may be due to higher growth vigor and excessive assimilates flowing to the root to withstand adverse growth conditions [ 8 ]. Our previous research has also confirmed that the formation of root tubers is accompanied by upregulation of starch genes and changes in sugar transporters [ 9 ]. Moreover, the nutrient-rich root tuber is being studied in depth.…”
Section: Introductionmentioning
confidence: 99%